THE INTERNET AND THE WORLD WIDE WEB ( WWW ) - BUZGAIA, MOHAMMED (The Libyan International Medical University - Faculty Of Information Technology, 2021)
The Internet, also called the Net, is aglobal computer network made up of thousands of privately and publicly owned computers and networks that grew and interlinked over time into one giant network. In short, the Internet is a network of networks
Keywords: THE INTERNET AND THE WORLD WIDE WEB